(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article discusses the methodological problem of language training for foreign students. It is emphasized that the study of the Ukrainian language as a foreign language should be focused on the formation of social and cultural competence of students to prepare them to different communicative situations. Expediency reading texts socio-cultural subjects, a sample of the text are examples posletekstovyh questions and tasks.